Osteoblastic Differentiation and Mitigation of the Inflammatory Response in Titanium Alloys Decorated with Oligopeptides - Aroa Álvarez-López; Raquel Tabraue-Rubio; Rafael Daza; Luis Colchero; Gustavo V. Guinea; Martine Cohen-Solal; José Pérez-Rigueiro; Daniel González-Nieto (Biomimetics)
Under benign conditions, bone tissue can regenerate itself without external intervention. However, this regenerative capacity can be compromised by various factors, most importantly related with the extent of the injury. Critical-sized defects, exceeding the body’s natural healing ability, demand the use of temporary or permanent devices like artificial joints or bone substitutes. While titanium is a widely used material for bone replacement, its integration into the body remains limited. This often leads to the progressive loosening of the implant and the need for revision surgeries, which are technically challenging, are commonly associated with high complication rates, and impose a significant economic burden. To enhance implant osseointegration, numerous studies have focused on the development of surface functionalization techniques to improve the response of the body to the implant. Yet, the challenge of achieving reliable and long-lasting prostheses persists. In this work, we address this challenge by applying a robust and versatile biofunctionalization process followed by the decoration of the material with oligopeptides. We immobilize four different peptides (RGD, CS-1, IKVAV, PHSRN) on R-THAB® functionalized surfaces and find them to be highly stable in the long term. We also find that RGD is the best-performing peptide in in vitro cell cultures, enhancing adhesion, proliferation, and osteogenic differentiation of mesenchymal stem cells. To assess the in vivo effect of RGD-decorated Ti-6Al-4V implants, we develop a calvarial model in murine hosts. We find that the RGD-decoration remains stable for 1 week after the surgical procedure and reduces post-implantation macrophage-related inflammation. These results highlight the potential of peptide decoration on R-THAB® functionalized surfaces to expedite the development of novel metallic biomaterials with enhanced biocompatibility properties, thereby advancing the field of regenerative medicine.